Online formative assessment practices among teachers - Ismawi, Nurkhuzaizah; Razali, Fazilah; Sulaiman, Tajularipin (Kalahari Journals, 2022)
Online Formative Assessment is now an important aspect of school management in Malaysia in line with digital developments in the world of education. The purpose of Formative Assessment is to track the level of mastery of students through Assessment for Learning and Assessment as Learning which is carried out continuously in teaching and learning either through oral, written or observation methods. However, the implementation of online formative assessment presents challenges to teachers especially in the aspect of facilities and skills to apply digital technology. Accordingly, this concept paper aims to discuss the practices and methods of online assessment performed by teachers as well as identify the digital skills of teachers in the aspects of the implementation of online assessment. This concept paper is constructed based on a literature review of several domestic and foreign articles related to online formative assessment and teachers ’digital skills in assessment. Based on the findings of the analysis from previous studies, formative assessment practices that are often used to assess students online are group discussions, portfolios, presentations and quizzes using Google Classroom, Google Meet, WhatsApp and Telegram applications while digital skills among teachers are at a moderate level. Thus, this concept paper also presents some suggestions for improving the quality of digital skills and teachers' strategies for online assessment.